UNCOVERING PATHOGENIC MISSENSE VARIANTS IN ENDOMETRIOSIS USING A GENOME-WIDE ASSOCIATION STUDY - Nurullita Santri, Ichtiarini; Adikusuma, Wirawan; Theda Philothra, Petrina; Fadhliati Maulida, Nurul; Chong, Rockie; Ates, Ilker; Vincent Abero Phiri, Yohane; Muhammad Irham, Lalu (JURNAL KESEHATAN REPRODUKSI, 2025)
Background: Endometriosis is a complex gynecological disorder with a strong genetic component. Although genome-wide association studies (GWAS) have identified numerous risk loci, the functional interpretation of protein-altering missense variants remains limited. Objective: This study identified pathogenic missense variants linked to endometriosis risk using publicly available GWAS data and explored implications for genetic risk detection, particularly in underrepresented populations such as Indonesia. Methods: Endometriosis-associated missense single nucleotide polymorphisms (SNPs) were identified from GWAS data, and a total of eight missense SNPs were analyzed. Functional effects were evaluated in silico using PolyPhen-2 and SIFT. Allele frequency distributions were assessed across global populations, and pathway enrichment analysis was conducted using the Reactome database. Results: Several missense variants were significantly associated with increased endometriosis risk (e.g., rs75801644, OR = 3.88; rs144824657, OR = 3.52), while rs2341097 showed a potential protective effect. Functional prediction prioritized variants in genes such as KCNG2 and BSG as potentially damaging. Population analyses revealed marked allele frequency differences, and enriched pathways were related to potassium channel activity, metabolism, extracellular matrix organization, and signal transduction. Conclusion: This study identifies missense variants contributing to endometriosis susceptibility and provides insight into biological pathways. Further experimental validation and clinical studies are warranted.